2016
DOI: 10.1080/14686996.2016.1239499
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of TiO2-polyethylene glycol nanoparticles stimulate proliferation of hepatocyte cells

Abstract: This paper describes the effect of low concentrations of 100 nm polyethylene glycol-modified TiO2 nanoparticles (TiO2-PEG NPs) on HepG2 hepatocellular carcinoma cells. Proliferation of HepG2 cells increased significantly when the cells were exposed to low doses (<100 μg ml–1) of TiO2-PEG NPs. These results were further confirmed by cell counting experiments and cell cycle assays. Cellular uptake assays were performed to determine why HepG2 cells proliferate with low-dose exposure to TiO2-PEG NPs. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Previously, our research showed that a low concentration of TiO 2 PEG NPs induces HepG2 cells to proliferate through the HGFR receptor aggregation [ 13 ], and we have also found that TiO 2 PEG NPs can induce A431 cell proliferation [ 14 ]. These findings suggested that TiO 2 PEG NPs could increase the risk of tumor overgrowth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, our research showed that a low concentration of TiO 2 PEG NPs induces HepG2 cells to proliferate through the HGFR receptor aggregation [ 13 ], and we have also found that TiO 2 PEG NPs can induce A431 cell proliferation [ 14 ]. These findings suggested that TiO 2 PEG NPs could increase the risk of tumor overgrowth.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is very beneficial to investigate the safety of TiO 2 PEG NPs as used in nanomedicine. Our previous research concluded that TiO 2 PEG NPs have a relatively low cellular uptake ratio [ 12 , 13 , 14 ]. In addition, TiO 2 PEG NPs induce HepG2 and A431 cell proliferation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an extensive distribution of lysosome and expression of endoplasmic reticulum proteins can be induced by anatase TiO 2 nanorods [128]. On the other hand, polymeric surface modifications can reduce or diminish hazard risks caused by the administration of TiO 2 nanomaterials [134][135][136][137]. The surface modifications may suppress the reactivity of crystals and minimize cellular and subcellular obstructive interactions [44,125,138].…”
Section: In Vitro Cytotoxicity Assessmentsmentioning
confidence: 99%